Method for preparing high-density solid electrolyte sheet by taking cross-linked polymer as template
By using crosslinked polymers as templates, combined with vacuum ball milling and hot pressing sintering technology, the problems of excessive pressure and low density in powder tableting method are solved, and high-efficiency and low-cost preparation of high-density solid electrolyte sheets and ceramics are achieved. The density and conductivity of the sheet are significantly improved.
Patent Information
- Application Number
- CN202411108520.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-20
AI Technical Summary
In the prior art, when preparing high-density solid electrolyte sheets by powder tableting method, the pressure is too high and the density is low, the equipment requirements are high, and the preparation efficiency and cost are high.
Using crosslinked polymer as template, mix polymer solution with solid electrolyte powder and additives by preparing vacuum ball milling, casting, scraping or casting, drying and hot-pressing crosslinking, and then using a high-temperature resistant plate. Sintered to remove the template and prepare a high density solid electrolyte sheet.
It has achieved low-cost and environmentally friendly preparation of high-density solid electrolyte sheets. The density of ceramic sheets can reach 97%, and the lithium-ion conductivity and activation energy are improved, reducing equipment requirements and preparation costs.
Smart Images

Figure CN119170857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template. Background Art
[0002] At present, there are mainly the following methods for preparing inorganic ceramic electrolyte sheets: tablet sintering, template method (including electrospinning, etc.), casting method (plasma sintering, etc.), 3D printing, etc. Tablet sintering, casting method and 3D printing have high requirements for equipment, low efficiency in sample preparation and high preparation cost. Among them, the method adopted by the majority of researchers is the tablet sintering method. Although this method can prepare high-density ceramic sheets (>96%), the efficiency of preparing electrolyte sheet samples by this method is extremely low. The pressed electrolyte precursor can generally obtain a dense ceramic sheet precursor under a large pressure (20MPa~800MPa). In addition, the electrolyte sheet obtained by tableting may also need to be cut, ground and polished depending on the method. The template method does not have high requirements for equipment. Choosing a suitable template can greatly reduce the preparation cost, and different templates can be selected to prepare ceramic sheets with different structures and densities. By designing the template, changing the slurry formula, adjusting the sintering temperature and other methods, a three-dimensional porous structure solid electrolyte sheet can be directly obtained. The templates used in the current template method are mainly some porous, ordered structure materials, such as dense wood, sponge and disordered structure prepared by electrospinning. However, the structure of these templates themselves is very loose, resulting in a very low density (<80%) of the prepared ceramic sheet. On this basis, the template used in the present invention is a cross-linked polymer network, and the density, thickness and three-dimensional structure of the solid electrolyte sheet are regulated by changing the polymer type, addition amount and sintering temperature.
[0003] In the prior art, the patent with publication number CN117525562A discloses solid electrolyte materials and preparation methods thereof, solid electrolyte sheets and all-solid-state batteries. The method for preparing solid electrolyte sheets is powder tableting, and the pressure applied by powder tableting is 20-100MPa; and the sintering process has been carried out during material synthesis, and the pressure of raw material tableting is 1-5GPa. It can be seen that the equipment required for tableting is high. Due to the limitation of the tablet press mold, laboratory-level tablet presses cannot be prepared in large quantities.
[0004] The patent with publication number CN116387610A discloses a lithium-containing solid electrolyte and its densification preparation method and application. It also adopts powder tablet sintering, mixes the solid electrolyte powder with a sintering aid, and presses it into a embryonic body. The applied pressure is 100-500MPa. Although powder tablet sintering is adopted, it can be observed through the cross-sectional SEM of its ceramic sheet that there are still many pores in the ceramic sheet, and the pore diameter is about 5-10μm, and the problem of low density is still prominent.
[0005] Therefore, the current preparation method of high-density solid electrolyte sheets still needs to be further improved. Summary of the invention
[0006] In view of this, the present invention proposes a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, which solves the technical problems of excessive powder tableting pressure, low density and complex and harsh cold sintering process in the prior art.
[0007] The technical solution of the present invention is achieved in this way:
[0008] The present invention provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0009] A high molecular polymer solution is prepared, and the high molecular polymer solution is mixed with solid electrolyte powder and an additive, and vacuum ball milling is performed to obtain a solid electrolyte / polymer composite slurry;
[0010] The solid electrolyte / polymer composite slurry is subjected to tape-casting, doctor blade coating or casting treatment, and then dried;
[0011] After drying, hot pressing is performed, and the temperature is raised or lowered to allow the polymer to be cross-linked to obtain a sheet-like solid electrolyte / polymer embryo, and then sliced;
[0012] The solid electrolyte / polymer embryo is pressed with a high temperature resistant plate, sintered, and the template of the cross-linked polymer is removed to obtain the high-density solid electrolyte sheet.
[0013] On the basis of this technical solution, further preferably, the preparation of the polymer solution comprises the following steps:
[0014] The high molecular polymer is weighed, dispersed in a solvent, and stirred to dissolve, thereby obtaining the high molecular polymer solution.
[0015] On the basis of this technical solution, it is further preferred that the high molecular polymer is one or a combination of any two or more of ethylene-vinyl acetate copolymer, polyacrylamide, polyvinyl pyrrolidone, polyvinyl alcohol, and water-based polyurethane.
[0016] On the basis of this technical solution, it is further preferred that the solvent is one of deionized water, N,N-dimethylformamide, xylene, ethanol, ethyl acetate, or a combination of any two or more thereof.
[0017] On the basis of this technical solution, it is further preferred that the solid electrolyte powder is one or a combination of two substances selected from the group consisting of LATP, LiPON, LGPS, LLZTO and LLZO, and has a particle size of 300 nm or 500 nm.
[0018] On the basis of this technical solution, further preferably, the conditions for the vacuum ball milling include a ball milling speed of 1000-3000 rpm and a ball milling time of 2-10 min.
[0019] On the basis of this technical solution, further preferably, the auxiliary agent includes a plasticizer, a leveling agent and a cross-linking agent.
[0020] On the basis of this technical solution, further preferably, the added amount of the plasticizer is 2-10% of the polymer solution, the added amount of the cross-linking agent is 1-5% of the polymer solution, and the added amount of the leveling agent is 0.2-2% of the polymer solution.
[0021] On the basis of this technical solution, it is further preferred that the drying is followed by hot pressing, wherein the hot pressing conditions include a hot pressing temperature of 60-120° C., a hot pressing time of 30-240 min, and a hot pressing pressure of 1-6 MPa.
[0022] On the basis of this technical solution, it is further preferred that the sintering temperature is 800-1000°C; the sintering heating rate is 2-10°C / min; the intermediate dwelling temperature is 300-500°C; and the dwelling time at the intermediate temperature is 10-60min.
[0023] On the basis of this technical solution, it is further preferred that the high temperature resistant plate is one or two of an aluminum oxide plate, a zirconium oxide plate, a mica plate or a mullite plate.
[0024] The method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template of the present invention has the following beneficial effects compared with the prior art:
[0025] In the present invention, LATP (Li 1.3 Al 0.3 Ti 1.7(PO4)3) electrolyte powder, and use low-cost and environmentally friendly solvents and polymers. The solid electrolyte / cross-linked polymer slurry can be prepared into embryos of different properties, sizes and thicknesses as needed. In addition, the content of solid electrolyte powder in the slurry determines the density of the solid electrolyte sheet after calcination. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a flow chart of the method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template according to the present invention;
[0028] Figure 2 This is a SEM image of the ceramic sheet prepared in Example 2-4 of the present invention;
[0029] Figure 3 The digital photo of the ceramic sheet in Example 2 and the XRD spectra of three LATP raw materials;
[0030] Figure 4 The Nyquist plot of the ceramic sheet after gold spraying in Example 2 and the activation energy data obtained by fitting the impedance data of the ceramic sheet;
[0031] Figure 5 The Nyquist plot of the ceramic sheet after gold spraying in Example 6 and the activation energy data obtained by fitting the impedance data of the ceramic sheet;
[0032] Figure 6 This is a schematic diagram of the electrochemical window of the LATP ceramic sheet of Example 6;
[0033] Figure 7 The Nyquist plot of the ceramic sheet after gold spraying in Comparative Example 1 and the activation energy data obtained by fitting the impedance data of the ceramic sheet;
[0034] Figure 8 This is a SEM image of the electrolyte sheet obtained in Comparative Example 1 of the prior art;
[0035] Fig. 9 This is a SEM image of the electrolyte sheet obtained in comparative example 2 of the prior art. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template. Figure 1 As shown, the following steps are included:
[0039] S1, preparing a high molecular polymer solution, mixing the high molecular polymer solution with solid electrolyte powder and additives, and vacuum ball milling to obtain a solid electrolyte / polymer composite slurry;
[0040] S2, the solid electrolyte / polymer composite slurry is subjected to tape casting, doctor blading or casting treatment, and then dried;
[0041] S3, hot pressing after drying, heating or cooling to allow the polymer to cross-link, to obtain a sheet-like solid electrolyte / polymer embryo, and slicing;
[0042] S4, using a high temperature resistant plate to press the solid electrolyte / polymer embryo, sintering, and removing the template of the cross-linked polymer to obtain the high-density solid electrolyte sheet.
[0043] In a preferred embodiment, the preparation of the polymer solution comprises the following steps:
[0044] The high molecular polymer is weighed, dispersed in a solvent, and stirred to dissolve, thereby obtaining the high molecular polymer solution.
[0045] In a preferred embodiment, the high molecular polymer is one or a combination of any two or more of ethylene-vinyl acetate copolymer, polyacrylamide, polyvinyl pyrrolidone, polyvinyl alcohol, and waterborne polyurethane.
[0046] In a preferred embodiment, the solvent is one of deionized water, N,N-dimethylformamide, xylene, ethanol, ethyl acetate, or a combination of any two or more thereof.
[0047] In a preferred embodiment, the solid electrolyte powder is one or a combination of two of LATP, LiPON, LGPS, LLZTO and LLZO, and has a particle size of 300 nm or 500 nm.
[0048] In a preferred embodiment, the vacuum ball milling conditions include a ball milling speed of 1000-3000 rpm and a ball milling time of 2-10 min.
[0049] In a preferred embodiment, the auxiliary agent includes a plasticizer, a leveling agent and a cross-linking agent.
[0050] In a preferred embodiment, the amount of the plasticizer added is 2-10% of the polymer solution, the amount of the cross-linking agent added is 1-5% of the polymer solution, and the amount of the leveling agent added is 0.2-2% of the polymer solution.
[0051] In a preferred embodiment, the drying is followed by hot pressing, wherein the hot pressing conditions include a hot pressing temperature of 60-120° C., a hot pressing time of 30-240 min, and a hot pressing pressure of 1-6 MPa.
[0052] In a preferred embodiment, according to different high molecular weight polymers, the specific polymer is made to reach the crosslinking temperature by heating or cooling, and crosslinking occurs. Specifically, after the hot pressing process is completed, according to the difference between the crosslinking temperature of the polymer and the hot pressing temperature, when the crosslinking temperature is higher than the hot pressing temperature, the temperature is increased to crosslink the polymer; when the crosslinking temperature is lower than the hot pressing temperature, the temperature is reduced to crosslink the polymer.
[0053] In a preferred embodiment, the high temperature resistant plate is one or two of an alumina plate, a zirconia plate, a mica plate or a mullite plate; the sintering temperature is 800-1000°C; the sintering heating rate is 2-10°C / min; the intermediate dwelling temperature is 300-500°C; and the dwelling time at the intermediate temperature is 10-60min.
[0054] Example 2
[0055] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0056] Prepare a high molecular polymer solution, weigh 10g polyvinyl alcohol and 90g deionized water, stir and disperse at room temperature for 2h, raise the temperature to 90-95℃ and continue stirring for 4h until the polyvinyl alcohol is completely dissolved, and set aside.
[0057] 4 g of LATP electrolyte powder was weighed and added to a customized PTFE ball mill, and 16 g of polyvinyl alcohol aqueous solution and an appropriate amount of zirconium beads were added, and the mixture was homogenized and ball milled at 2000 rpm in a vacuum homogenizer for 2 min.
[0058] The uniformly mixed slurry was taken out, and 0.16 g of glutaraldehyde, 0.4 g of propylene glycol, and 0.1 g of a leveling agent were added, and the PTFE ball mill was placed in a homogenizer and homogenized at 1000 rpm for 2 minutes under vacuum.
[0059] The evenly mixed composite slurry was poured into a circular polytetrafluoroethylene mold with an inner diameter of 9 cm and a height of 5 mm, and low-temperature drying was performed at 35° C. for 12 h to obtain the LATP embryo (LATP / PVA composite material).
[0060] The warped part of the edge of the LATP embryo was cut off, and the embryo was hot pressed at 90°C for 90 minutes with a pressure of 5 MPa to obtain a flat LATP embryo. The LATP ceramic sheet precursor was cut out using a 19 mm slicing knife.
[0061] The LATP ceramic sheet precursor was placed in a box furnace and sintered in an air atmosphere to remove the cross-linked polymer template. The sintering conditions were a heating rate of 2°C / min, and after staying at 300°C for 10 minutes, the temperature was continuously raised to 850°C and kept for 120 minutes, finally obtaining a LATP ceramic sheet with a diameter of 15-16 mm.
[0062] Results: Figure 2 This is a SEM image of the ceramic sheet prepared in Example 2-4 of the present invention; Figure 3 The digital photo of the ceramic sheet in Example 2 and the XRD spectra of the three LATP raw materials are shown in FIG. Figure 2 It can be seen that the electrolyte sheet prepared in Example 2 has good density. At different calcination temperatures, the ceramic sheet particles show different particle sizes and connection modes between particles. As the calcination temperature increases, the ceramic sheet particles gradually become larger, and the particle connection mode changes from individual connection between particles to large-scale particle welding. Figure 3 As can be seen from (a) in Example 2, the surface of the ceramic sheet obtained is smooth and flat, without obvious macroscopic defects, and can be prepared into suitable sizes and shapes according to application requirements (the ceramic sheet in the figure is suitable for button batteries of models such as 2025 and 2032). Figure 3 In (b), it can be seen that the three LATP raw materials in Example 2 are consistent with the standard PDF card and have the same crystal form, indicating that electrolyte materials from different sources can be used to prepare electrolyte sheets using the method of the present invention. Figure 4 and Figure 5 It can be seen that the calcination temperature of the ceramic sheet precursor affects its lithium ion conductivity and activation energy. Combined with the data in Table 1, it can be seen that at a suitable calcination temperature, the obtained ceramic sheet has a higher density, and the ceramic sheet therefore has better lithium ion conductivity.
[0063] Example 3
[0064] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0065] Prepare a high molecular polymer solution, weigh 10g polyvinyl alcohol and 90g deionized water, stir and disperse at room temperature for 2h, raise the temperature to 90-95℃ and continue stirring for 4h until the polyvinyl alcohol is completely dissolved, and set aside.
[0066] 4 g of LATP electrolyte powder was weighed and added to a customized PTFE ball mill, and 16 g of polyvinyl alcohol aqueous solution and an appropriate amount of zirconium beads were added, and the mixture was homogenized and ball milled at 2000 rpm in a vacuum homogenizer for 2 min.
[0067] The uniformly mixed slurry was taken out, and 0.16 g of glutaraldehyde, 0.4 g of propylene glycol, and 0.1 g of a leveling agent were added, and the PTFE ball mill was placed in a homogenizer and homogenized at 1000 rpm for 2 minutes under vacuum.
[0068] The evenly mixed composite slurry was poured into a circular polytetrafluoroethylene mold with an inner diameter of 9 cm and a height of 5 mm, and low-temperature drying was performed at 35° C. for 12 h to obtain the LATP embryo (LATP / PVA composite material).
[0069] The warped part of the edge of the LATP embryo was cut off, and the embryo was hot pressed at 90°C for 90 minutes with a pressure of 5 MPa to obtain a flat LATP embryo. The LATP ceramic sheet precursor was cut out using a 19 mm slicing knife.
[0070] The LATP ceramic sheet precursor was placed in a box furnace and sintered in an air atmosphere to remove the cross-linked polymer template. The sintering conditions were a heating rate of 10°C / min, staying at 500°C for 60 minutes and then continuing to heat to 850°C and keeping warm for 120 minutes, finally obtaining a LATP ceramic sheet with a diameter of 15-16 mm.
[0071] Example 4
[0072] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0073] Prepare a high molecular polymer solution, weigh 10g polyvinyl alcohol and 90g deionized water, stir and disperse at room temperature for 2h, raise the temperature to 90-95℃ and continue stirring for 4h until the polyvinyl alcohol is completely dissolved, and set aside.
[0074] 4 g of LATP electrolyte powder was weighed and added to a customized PTFE ball mill, and 16 g of polyvinyl alcohol aqueous solution and an appropriate amount of zirconium beads were added, and the mixture was homogenized and ball milled at 2000 rpm in a vacuum homogenizer for 2 min.
[0075] The uniformly mixed slurry was taken out, and 0.16 g of glutaraldehyde, 0.4 g of propylene glycol, and 0.1 g of a leveling agent were added, and the PTFE ball mill was placed in a homogenizer and homogenized at 1000 rpm for 2 minutes under vacuum.
[0076] The evenly mixed composite slurry was poured into a circular polytetrafluoroethylene mold with an inner diameter of 9 cm and a height of 5 mm, and low-temperature drying was performed at 35° C. for 12 h to obtain the LATP embryo (LATP / PVA composite material).
[0077] The warped part of the edge of the LATP embryo was cut off, and the embryo was hot pressed at 90°C for 90 minutes with a pressure of 5 MPa to obtain a flat LATP embryo. The LATP ceramic sheet precursor was cut out using a 19 mm slicing knife.
[0078] The LATP ceramic sheet precursor was placed in a box furnace and sintered in an air atmosphere to remove the cross-linked polymer template. The sintering conditions were a heating rate of 6°C / min, and after staying at 400°C for 35 minutes, the temperature was continuously raised to 900°C and kept for 120 minutes, finally obtaining a LATP ceramic sheet with a diameter of 15-16 mm.
[0079] Example 5
[0080] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0081] Prepare a high molecular polymer solution, weigh 10g polyvinyl alcohol and 90g deionized water, stir and disperse at room temperature for 2h, raise the temperature to 90-95℃ and continue stirring for 4h until the polyvinyl alcohol is completely dissolved, and set aside.
[0082] 4 g of LATP electrolyte powder was weighed and added to a customized PTFE ball mill, and 16 g of polyvinyl alcohol aqueous solution and an appropriate amount of zirconium beads were added, and the mixture was homogenized and ball milled at 2000 rpm in a vacuum homogenizer for 2 min.
[0083] The uniformly mixed slurry was taken out, and 0.16 g of glutaraldehyde, 0.4 g of propylene glycol, and 0.1 g of a leveling agent were added, and the PTFE ball mill was placed in a homogenizer and homogenized at 1000 rpm for 2 minutes under vacuum.
[0084] The evenly mixed composite slurry was poured into a circular polytetrafluoroethylene mold with an inner diameter of 9 cm and a height of 5 mm, and low-temperature drying was performed at 35° C. for 12 h to obtain the LATP embryo (LATP / PVA composite material).
[0085] The warped part of the edge of the LATP embryo was cut off, and the embryo was hot pressed at 90°C for 90 minutes with a pressure of 5 MPa to obtain a flat LATP embryo. The LATP ceramic sheet precursor was cut out using a 19 mm slicing knife.
[0086] The LATP ceramic sheet precursor was placed in a box furnace and sintered in an air atmosphere to remove the cross-linked polymer template. The sintering conditions were a heating rate of 2°C / min, and after staying at 500°C for 10 minutes, the temperature was continuously raised to 900°C and kept for 120 minutes, finally obtaining a LATP ceramic sheet with a diameter of 15-16 mm.
[0087] Example 6
[0088] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0089] Prepare a high molecular polymer solution, weigh 10g polyvinyl alcohol and 90g deionized water, stir and disperse at room temperature for 2h, raise the temperature to 90-95℃ and continue stirring for 4h until the polyvinyl alcohol is completely dissolved, and set aside.
[0090] 4 g of LATP electrolyte powder was weighed and added to a customized PTFE ball mill, and 16 g of polyvinyl alcohol aqueous solution and an appropriate amount of zirconium beads were added, and the mixture was homogenized and ball milled at 2000 rpm in a vacuum homogenizer for 2 min.
[0091] The uniformly mixed slurry was taken out, and 0.16 g of glutaraldehyde, 0.4 g of propylene glycol, and 0.1 g of a leveling agent were added, and the PTFE ball mill was placed in a homogenizer and homogenized at 1000 rpm for 2 minutes under vacuum.
[0092] The evenly mixed composite slurry was poured into a circular polytetrafluoroethylene mold with an inner diameter of 9 cm and a height of 5 mm, and low-temperature drying was performed at 35° C. for 12 h to obtain the LATP embryo (LATP / PVA composite material).
[0093] The warped part of the edge of the LATP embryo was cut off, and the embryo was hot pressed at 90°C for 90 minutes with a pressure of 5 MPa to obtain a flat LATP embryo. The LATP ceramic sheet precursor was cut out using a 19 mm slicing knife.
[0094] The LATP ceramic sheet precursor was placed in a box furnace and sintered in an air atmosphere to remove the cross-linked polymer template. The sintering conditions were a heating rate of 10°C / min, staying at 300°C for 60 minutes and then continuing to heat to 900°C and keeping warm for 120 minutes, finally obtaining a LATP ceramic sheet with a diameter of 15-16 mm.
[0095] result: Figure 5 The Nyquist plot of the ceramic sheet after gold spraying in Example 6 and the activation energy data obtained by fitting the impedance data of the ceramic sheet are shown in FIG. Figure 6The schematic diagram of the electrochemical window of the LATP ceramic sheet impregnated with PEO polymer shows that the ceramic sheet with a connected three-dimensional porous structure can be better combined with the flexible polymer. Compared with the dense ceramic sheet obtained by sintering after powder tableting, the ceramic sheet in the present invention forms an embedded combination at its interface after being impregnated with the polymer solution, which increases the contact between the interfaces and reduces the impedance between the interfaces. In addition, the flexible PEO is embedded in the rigid ceramic sheet to form a "quasi-composite material" structure, which has the advantages of both materials.
[0096] Example 7
[0097] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0098] Prepare a high molecular polymer solution, weigh 10g polyvinyl alcohol and 90g deionized water, stir and disperse at room temperature for 2h, raise the temperature to 90-95℃ and continue stirring for 4h until the polyvinyl alcohol is completely dissolved, and set aside.
[0099] 4 g of LATP electrolyte powder was weighed and added to a customized PTFE ball mill, and 16 g of polyvinyl alcohol aqueous solution and an appropriate amount of zirconium beads were added, and the mixture was homogenized and ball milled at 2000 rpm in a vacuum homogenizer for 2 min.
[0100] The uniformly mixed slurry was taken out, and 0.16 g of glutaraldehyde, 0.4 g of propylene glycol, and 0.1 g of a leveling agent were added, and the PTFE ball mill was placed in a homogenizer and homogenized at 1000 rpm for 2 minutes under vacuum.
[0101] The evenly mixed composite slurry was poured into a circular polytetrafluoroethylene mold with an inner diameter of 9 cm and a height of 5 mm, and low-temperature drying was performed at 35° C. for 12 h to obtain the LATP embryo (LATP / PVA composite material).
[0102] The warped part of the edge of the LATP embryo was cut off, and the embryo was hot pressed at 90°C for 90 minutes with a pressure of 5 MPa to obtain a flat LATP embryo. The LATP ceramic sheet precursor was cut out using a 19 mm slicing knife.
[0103] The LATP ceramic sheet precursor was placed in a box furnace and sintered in an air atmosphere to remove the cross-linked polymer template. The sintering conditions were a heating rate of 5°C / min, staying at 300°C for 10 minutes and then continuing to heat to 900°C and keeping warm for 120 minutes, finally obtaining a LATP ceramic sheet with a diameter of 15-16 mm.
[0104] Comparative Example 1
[0105] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0106] Prepare a high molecular polymer solution, weigh 10g of ethylene-vinyl acetate copolymer and 70g of xylene, stir and disperse at 60°C for 2h, raise the temperature to 60°C and continue stirring for 2h to dissolve the ethylene-vinyl acetate copolymer, and set aside.
[0107] 4 g of LLZTO electrolyte powder was weighed and added to a customized PTFE ball mill, and 16 g of ethylene-vinyl acetate copolymer solution and an appropriate amount of zirconium beads were added, and the mixture was homogenized and ball milled at 2000 rpm in a vacuum homogenizer for 2 min.
[0108] The uniformly mixed slurry was taken out, and 0.16 g of aziridine, 0.4 g of tributyrin, and 0.1 g of leveling agent 2 were added, and the PTFE grinding jar was placed in a homogenizer and homogenized at 1000 rpm for 2 minutes under vacuum.
[0109] The evenly mixed composite slurry was poured into a circular polytetrafluoroethylene mold with an inner diameter of 9 cm and a height of 5 mm, and dried at 60° C. for 12 h to obtain a LLZTO embryo (LATP / EVA composite material).
[0110] The green body was hot pressed at 90°C for 90 minutes at a pressure of 5 MPa to obtain a flat LLZTO green body, and a LATP ceramic sheet precursor was cut out using a 19 mm slicing knife.
[0111] The LLZTO ceramic sheet precursor was placed in a box furnace and sintered in an air atmosphere to remove the cross-linked polymer template. The sintering conditions were 2°C / min and 1000°C for 120 min, and finally a LATP ceramic sheet with a diameter of 14-15 mm was obtained.
[0112] result: Figure 7 The Nyquist plot of the ceramic sheet after gold spraying and the activation energy data obtained by fitting the impedance data of the ceramic sheet in Comparative Example 1. It can be seen that for other types of solid electrolyte materials, this method can also be used to prepare electrolyte sheets, and their lithium ion conductivity and activation energy are both at a high level.
[0113] Comparative Example 2
[0114] This embodiment provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, comprising the following steps:
[0115] Prepare PEO / LITFSI solution: weigh 1 g PEO (MW=600000) and 0.815 g LITFSI in a sample bottle, add 40 ml acetonitrile and stir magnetically at room temperature until PEO and LITFSI are completely dissolved; vacuum defoam the polymer solution and seal it for later use.
[0116] LATP ceramic sheet pretreatment: The sintered ceramic sheet needs to be vacuum dried at 80°C for 12 h before drop coating of the polymer solution and transferred to a glove box for storage.
[0117] 0.2 g of PEO / LITFSI solution was drop-coated on both sides of the LATP electrolyte sheet, and acetonitrile was evaporated at room temperature. The LATP electrolyte sheet with the polymer interface layer was then transferred to a vacuum oven and vacuum-dried at 60°C for 12 h to obtain a composite LATP solid electrolyte sheet.
[0118] A 0.5 mm thick stainless steel sheet was used as a blocking electrode and assembled with a composite LATP electrolyte sheet into a 2032 button cell for electrochemical impedance spectroscopy.
[0119] result: Figure 8 (a) and (b) in , and Fig. 9 (a) and (b) are SEM images of composite electrolytes prepared by the prior art template method and solution method. Compared with the present invention, the upper and lower layers of polymers have the disadvantage of high porosity.
[0120] Table 1 Performance test of ceramic sheets in various embodiments and comparative examples
[0121]
[0122] In summary, the present invention provides a method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template. The density of the LATP ceramic sheet prepared by the above method can reach up to 97%, and the ionic conductivity of the ceramic sheet is 1.59×10 -4 S / cm, and the activation energy is 0.167 eV.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-density solid electrolyte sheet using a cross-linked polymer as a template, It is characterized in that The steps include: A high molecular polymer solution is prepared, and the high molecular polymer solution is mixed with solid electrolyte powder and an additive, and vacuum ball milling is performed to obtain a solid electrolyte / polymer composite slurry; The solid electrolyte / polymer composite slurry is subjected to tape-casting, doctor blade coating or casting treatment, and then dried; After drying, hot pressing is performed, and the temperature is raised or lowered to allow the polymer to be cross-linked to obtain a sheet-like solid electrolyte / polymer embryo, and then sliced; The solid electrolyte / polymer embryo is pressed with a high temperature resistant plate, sintered, and the template of the cross-linked polymer is removed to obtain the high-density solid electrolyte sheet.
2. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 1, It is characterized in that The preparation of the high molecular polymer solution comprises the following steps: The high molecular polymer is weighed, dispersed in a solvent, and stirred to dissolve, thereby obtaining the high molecular polymer solution.
3. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 2, It is characterized in that The high molecular polymer is one of ethylene-vinyl acetate copolymer, polyacrylamide, polyvinyl pyrrolidone, polyvinyl alcohol, and waterborne polyurethane, or a combination of any two or more of the above.
4. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 2, It is characterized in that The solvent is one of deionized water, N,N-dimethylformamide, xylene, ethanol, ethyl acetate, or a combination of any two or more of the above substances.
5. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 1, It is characterized in that The solid electrolyte powder is one or a combination of two of LATP, LiPON, LGPS, LLZTO and LLZO, and has a particle size of 300 nm or 500 nm.
6. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 2, It is characterized in that The vacuum ball milling conditions include a ball milling speed of 1000-3000 rpm and a ball milling time of 2-10 min.
7. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 1, It is characterized in that The auxiliary agents include plasticizers, leveling agents and cross-linking agents.
8. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 7, It is characterized in that The added amount of the plasticizer is 2-10% of the high molecular polymer solution, the added amount of the cross-linking agent is 1-5% of the high molecular polymer solution, and the added amount of the leveling agent is 0.2-2% of the high molecular polymer solution.
9. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 1, It is characterized in that The hot pressing after drying, wherein the hot pressing conditions include: the hot pressing temperature is 60-120° C., the hot pressing time is 30-240 min, and the hot pressing pressure is 1-6 MPa.
10. A method for preparing a high-density solid electrolyte sheet using the cross-linked polymer as a template according to claim 1, It is characterized in that The sintering temperature is 800-1000° C.; the sintering heating rate is 2-10° C. / min; the intermediate dwelling temperature is 300-500° C.; and the dwelling time at the intermediate temperature is 10-60 min.
Citation Information
Patent Citations
Lithium-containing solid electrolyte and densification preparation method and application thereof
CN116387610A
Solid electrolyte material and preparation method thereof, solid electrolyte sheet and all-solid-state battery
CN117525562A
